(untitled) (Revista Innova Educación, 2024)
In this study, is compared the effectiveness of three educational methodologies: Education 4.0, traditional education and e-learning, in the development of investigative and statistical skills among university students. A quantitative-qualitative investigation was carried out with a sample of 96 students from the University of Aconcagua (Chile) during the period between August and December 2023. Data collection was carried out through "ad hoc" surveys, designed to meet with standards of validity and reliability. The results indicate that the use of Education 4.0 demonstrated a significant increase in statistical competencies, particularly in the use of Power BI software, reaching 73.61%, in contrast to the 5.56% observed in students who only used e-learning (p< 0.001). Furthermore, the evaluation of statistical competencies for research, measured on a scale from 1 to 5, where 5 represents the maximum level, obtained an average of 4,355 in the group that applied the methodology with Education 4.0, significantly exceeding the 3,429 obtained with the traditional method (p<0.05). In conclusion, the findings suggest that Education 4.0 is a more effective strategy than e-learning and traditional teaching for the development of statistical and research skills. These results provide solid foundations to promote an innovative and practical approach in the comprehensive training of future professionals.